PENGARUH ALOKASI DANA DESA TERHADAP PEREKONOMIAN MASYARAKAT DESA KABUPATEN MUSI BANYUASIN PROPINSI SUMATERA SELATAN - Agustina, Yumniati; Cusyana, Silvi Reni (Ekonomi & Bisnis, 2018)
Law No. 6 of 2014 explains that the Village Fund Allocation is a part of the balancing funds received by the kabupaten / kota in APBD after deducting the special allocation fund. The objectives of ADD / K are listed in MUBA REVOCATION No.15 of 2013, No. 4 of 2014 and PERMENDESA No.21 of 2015 concluded that village funds are prioritized to improve the economy of rural communities and target the use of ADD / K, including: salary / allowances, honoraria Village Management Team and Activity Implementation Team, village operational expenditure, community productive economic empowerment and physical development expenditure. This research analyzes the influence of each target of village fund allocation to the economics of the village community of MUBA Regency and the influence of the joint. Using path analysis Technique, research object 240 villages. The village economy is proxied in per capita income by the number of villagers in 2013 and 2014.Â  The results showed that: the target variable for the use of the village fund allocation for honorarium TPKD and TPK have constant data, thus omitted from the relationship model; salary / benefit financing has significant effect of 29.24%; village operational costs have a significant effect of -3.35%; community productive economic empowerment expenditure has no significant effect because there is a close correlation between this variable with physical development expenditure, so it can be represented by physical construction expenditure which have significant effect of 65,01%; the shared use of allocation of village funds has a significant effect of 68.3%.